Sam and the tigers : a new telling of Little Black Sambo - Lester, Julius, 1939-2018.; Pinkney, Jerry; Bannerman, Helen, 1862-1946. (New York : Puffin Books, 2000)
Follows the adventures of a little boy named Sam when he matches wits with several tigers that want to eat him.
Keywords: Tiger -- Fiction; Humorous stories